Ownership, control and ideology: an enquiry into certain aspects of modern business ideology - Nichols, Theo (London, 1969)
"UK. Analysis of an occupational sociology survey of managers in Britain - comprises three sections on (1) theoretical views of managerialism, (2) the ownership control controversy (incl. The occupational qualifications, social status and behaviour of new managers) and (3) the sociological aspects of business ideology and ethics, and includes the text of the questionnaire used. Bibliography pp. 256 to 264, references and statistical tables."